Data crunch report: The impact of bad data on profits and customer service in the UK grocery industry - GS1 UK; IBM; The Institute of Grocery Distribution; Cranfield School of Management, (KTP project); Value Chain Vision (GS1 UK and Cranfield University School of Management, 2009)
The UK retail industry is behind the curve in addressing the challenge of poor product supply chain data. The size of the quality problem is a lot worse than expected, with data shown to be inconsistent in over 80% of instances. It is estimated that this will cost the industry at least £700m over the next 5 years, and a further £300m in lost revenues. Looking forward, consumers are demanding better product information and labelling for nutrition, health and lifestyle. Planned European legislation is also demanding that the industry provides further information related to packaging and the environment. In this future world manual work arounds and pragmatic fixes employed currently by retailers are no longer sustainable. The time has arrived for the UK grocery industry to address the data quality issue head on, and reap the considerable benefits.